2022
DOI: 10.1186/s10020-022-00541-1
|View full text |Cite
|
Sign up to set email alerts
|

ZNF384–ZEB1 feedback loop regulates breast cancer metastasis

Abstract: Background Breast cancer has become the most frequently diagnosed cancer worldwide. Increasing evidence indicated that zinc finger proteins (ZNFs), the largest family of transcription factors, contribute to cancer development and progression. Although ZNF384 is overexpressed in several types of human cancer, the role of ZNF384 in breast cancer remains unknown. Therefore, our research focused on ZNF384 regulation of the malignant phenotype of breast cancer and the underlying molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It is reported that overexpression of ZNF384 has oncogenic potential for some solid tumors, such as hepatocellular carcinoma and breast cancer. 22 , 23 Because Z‐fusion proteins contain all of ZNF384, it is expected that the DNA binding sites are quite similar between them.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that overexpression of ZNF384 has oncogenic potential for some solid tumors, such as hepatocellular carcinoma and breast cancer. 22 , 23 Because Z‐fusion proteins contain all of ZNF384, it is expected that the DNA binding sites are quite similar between them.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have explored a possible cancer-promoting activity of the transcription factor ZNF384 in different cancers. Meng et al showed that ZNF384 is upregulated in breast cancer and is important for cancer cell metastasis [ 36 ]. ZNF384 is possible transcription factor for the histone acetyltransferase HBO1, the latter promoted osteosarcoma cell growth in vitro and in vivo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation was measured using the CCK-8 kit (Yeasen, Shanghai, China) as previously described 34 .…”
Section: Cell Counting Kit-8 (Cck-8) Assays Of Cell Viabilitymentioning
confidence: 99%